Comics and Zines for Creative Research Impact: Ethics, Politics and Praxis in Geographical Research - Sou, Gemma; Hall, Sarah Marie (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2023)
We contribute to critical debates about the ethics, politics and praxis of research impact by drawing on our experiences of translating research into a comic and a zine. We demonstrate how comics and zines construct ethical and nuanced depictions of socio-politically marginalised groups, moving away from ‘damage centred’ research frameworks. Comics and zines enable readers to access places and moments that other mediums are less able to, and they gesture toward a participatory, slowed-down practice of research engagement. Finally, we suggest that current indicators of impact ought to consider the methods and praxis of impact, rather than focus on measurements related to outputs, as a way to creatively encourage research to meaningfully engage with participants and publics.